Lymphovascular space invasion as a prognostic determinant in uterine cancer. - Cheewakriangkrai C. (2014)
The objective of this study was to evaluate the clinical significance of lymphovascular space invasion (LVSI) in patients with uterine cancer in terms of lymph node metastasis, recurrence and survival rate. A total of 190 patients with newly diagnosed uterine cancer who underwent total abdominal hysterectomy (TAH), bilateral salpingo-oophorectomy (BSO), omentectomy, peritoneal washing or ascitic fluid collection, and pelvic/paraaortic lymph node sampling at Chiang Mai University Hospital between January 1999 and December 2004 were evaluated. All medical records and histopathologic slides were retrospectively reviewed to determine the relationship between LVSI and clinicopathological characteristics. LVSI was present in 79 patients (42%) and significantly correlated with lymph node metastasis (p0.001), BMI 25 kg/m2 (p0.001), advanced FIGO stage (p 0.001), poor histologic grade (p0.001), and deep uterine invasion (p0.001). Patients with LVSI, when stratified by FIGO stage, also had a significant lower 5-year survival rate. For those who had disease recurrence, LVSI and histologic grade were found to be independent prognostic factors in a multivariate analysis. LVSI was one of the prognostic determinants for disease recurrence and associated with poor survival in patients with uterine cancer.